SOSIALISASI KURIKULUM PEMBINAAN SEPAKBOLA INDONESIA DI KABUPATEN SIAK - Ricky Fernando; Tomi Erfando; Anggea Titania; Ade Irma (Bajang Institute, 2022)
The Indonesian football coaching curriculum aims to serve as a guide for teachers and coaches at an early age and young age on how to provide appropriate and appropriate stages of training according to age levels. To strengthen and develop the philosophy of Indonesian football, it takes a touch of Sports Science that is thick in Indonesian football culture. The Indonesian football coaching curriculum also describes the stages of coaching in which each stage has systematic and specific training methods according to the needs of the age level. The stages of coaching in the Indonesian football curriculum prepare players who are capable of playing football. compose a logical and simple football to make it easier for players to understand the game of football. The coach's understanding of the football coaching curriculum is the key in shaping the character and development of players from an early age and young age, in essence, all phases that are passed in football coaching are designed as a contribution to print players in elite pro clubs and professional players. strong and able to compete at international level.